Managerial Reputation and Internal Reporting. - Sridhar, Sri S. (The Accounting Review, 1994)
Abstract Demonstrates how a manager's concern for reputation can distort reports made to superiors about an investment project and affect a firm's capital budgeting decisions. Managerial investment distortion in the choice between short term and long term projects; Underinvestment of the firm as a result of managerial misreporting; Participative budgeting issues.